PENGARUH LABEL HALAL TERHADAP KEPUTUSAN PEMBELIAN DENGAN RELIGIUSITAS SEBAGAI VARIABEL INTERVENING DI MUJIGAE RESTO BANDUNG - Ananda Desmayonda; Arlin Ferlina Mochamad Trenggana (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, Korean Restaurants that have been labeled halal are still few.For the city of Bandung one of them is Mujigae Resto. This study aims to find out and analyze halal, religiosity and purchasing decisions so that it is expected to attract consumers not only Muslims but also non-Muslims because of the guarantee of halal products. This research is a quantitative descriptive - causal study with an unknown number of Mujigae Resto Bandung populations. Respondents numbered 100 people taken by non-probability sampling technique type of accidental sampling and data analysis using path analysis. Based on the results of data processing, it is known that halal labels and purchasing decisions fall into the "good" category with a value range of 68% - 84%, while religiosity falls into the "very good" category. Halal labels have an influence on religiosity of 57.6%, but have no influence on purchasing decisions. While religiosity has an influence on purchasing decisions of 19,3%. The effect of halal labels on purchasing decisions through religiosity is 68,7% while the remaining 31,3% is influenced by other variables not examined in the study.